바렛식도와 이형성증, 조기식도선암의 진단과 치료: 미국과 유럽의 임상지침을 중심으로 - 유아영; Ah Young Yoo; 주문경; Moon Kyung Joo (The Korean journal of gastroenterology, 2019)
Barrett’s esophagus (BE) is one of the most prominent diseases in Western countries because of its potential to progress to dysplasia or adenocarcinoma. Recently, the American College of Gastroenterology (ACG), American Gastroenterology Association (AGA), and European Society of Gastrointestinal Endoscopy (ESGE) developed clinical guidelines for the diagnosis and management of BE. All three guidelines commonly stressed the necessity of the endoscopic eradication of confirmed, nonnodular low grade dysplasia or high grade dysplasia, as well as the endoscopic elimination of the remaining BE after an endoscopic resection of visible mucosal abnormalities. An endoscopic resection is also considered for the optimal management of esophageal adenocarcinoma confined to the mucosa (T1a), and even in selective cases of submucosal invasion (T1b). As endoscopic therapy becomes the mainstay for the treatment of BE and its complications, the eligibility of pathologic or endoscopic experts and the BE expert center are being set and strengthened. This paper introduces the statements of the ACG, AGA and ESGE guidelines and compares the similarities and differences between them. (Korean J Gastroenterol 2019;74:11-16)